Influence of Electronic Media: The Impact of Electronic Media on Reading Culture and Lifelong Learning (Journal of Advances and Scholarly Researches in Allied Education, 2012)
Reading is an essential tool for lifelonglearning. It is important for everyone to develop the rudiments of reading andthe culture of reading always so as to survive in life.